(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper we will discuss about study on the effectiveness of vocational occupational rehabilitation therapy of the traumatic paraplegic patients” this chapter helped investigator to develop tool, analysis and interpretation of the data. Review of literature suggests that there is need to conduct the study on comprehensive aspects of rehabilitation. This chapter dealt with the research approach, setting, target population, sample and sampling technique, selection and development of tools, description of tools, pilot study, and procedure for data collection and plan for data analysis.